Konsep Wasathiyyah M. Quraish Shihab dalam Tafsir Al-Misbah (Analisis Hermeneutika Hans-Georg Gadamer) - Nur Huda; Nur Hamid; Muhammad Khoirul Misbah (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2020)
The Islamic world, especially Indonesia, is increasingly experiencing moral and mental decline so that life is increasingly far from Islamic values. The emergence of extreme ideas and deviating from the truth also added to the atmosphere. It is wasaṭhiyyah, a moderate attitude in various aspects of life that is slowly being echoed by Muslim scholars in various parts of the world and is used as a powerful formula in dealing with the above problems. This research tries to discuss the concept of wasaṭhiyyah according to M. Quraish Shihab in Tafsir Al-Misbah. This research is classified as library research. The researcher used Hans-Georg Gadamer's hermeneutic analysis. With this analysis knife, the researcher found that the Tafsir Al-Misbah was written as a response to M. Quraish Shihab's response to the phenomena and conflicts that occurred at that time. The fusion between Shihab's understanding of wasaṭhiyyah with various horizons; text and society produces a concept of wasaṭhiyyah which is a fair, balanced and tolerant attitude in life, both in world and in the hereafter